2010
DOI: 10.1080/19361521.2010.500984
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Shy Voices: Shy Adolescents’ Experiences with Being Bullied at School

Abstract: This study examined bullying related to adolescents exhibiting shyness as an emotional and behavioral problem in the school context. It is based on in-depth interviews and observations of severely shy girls between the ages of 14 and 18 years. Given this group of students' difficulties with social skills, peer rejection, and victimization, we sought to explore (a) the form that bullying takes, (b) the genders commonly represented among aggressors, and (c) the reasons that shy adolescents give for being bullied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 62 publications
(98 reference statements)
2
10
0
1
Order By: Relevance
“…Being ignored and excluded from social settings can be connected to bullying. Subsequently, this study confirms earlier research underlining the connection between bullying and its effect on students with SEBD (Lund et al., 2010; Olweus, 1993) and bullying and dropout (Bauman and Del Rio, 2005).…”
Section: Findings and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Being ignored and excluded from social settings can be connected to bullying. Subsequently, this study confirms earlier research underlining the connection between bullying and its effect on students with SEBD (Lund et al., 2010; Olweus, 1993) and bullying and dropout (Bauman and Del Rio, 2005).…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Among the students with internalised problems, there were three (out of a total of five) who maintained that their dropout behaviour was caused by non‐supportive teachers and classroom environments in both the past and the present. These findings correlate with earlier research related to this adolescent group's experiences with adults and peers at school (Bauman and Del Rio, 2005; Lund, Ertesvåg and Roland, 2010; Ogden, 2001).…”
Section: Findings and Discussionsupporting
confidence: 89%
“…Various studies have been carried out which indicate the prevalence of bullying, for example, a meta-analysis was conducted which indicated that 36% of participants were involved in traditional bullying, while 15% were found the victims through social media (Modecki, Minchin, Harbaugh, Guerra, & Runions, 2014). Among the victims, some approach their bully, to stop them by mentioning their concerns to the related behaviour (Brent, 2016), and some avoid their bully to keep themselves safe from further victimization (Lund, Ertesvåg, & Roland, 2010). Another study of 269 undergraduate students indicated that, students who were bullied in early age felt excluded and rejected from their society.…”
Section: Bullying Victimmentioning
confidence: 99%
“…There are many example scenarios that can address this kind of reaction or strategy chosen by a victim. For example, 'They called me bad names, and I didn't know what else to do than walk away from them' (Lund et al, 2010). This example scenario is shown in the simulation results that are depicted in Figure 3.…”
Section: Avoidance Strategymentioning
confidence: 99%
“…Der laerere utsetter elever for mobbing, vil det ofte vaere ulike virkelighetsoppfatninger av hva som har skjedd i mobbesituasjonen. Studier der barn og unge blir intervjuet om mobbing, viser at ulike virkelighetsoppfatninger er grunnlag for manglende tiltak og oppfølging ifølge elevene selv (Lund, Ertesvåg & Roland, 2010;Frisen, Holmquist & Oscarsson, 2008)). Ifølge Bang (2013) er virkelighetsoppfatninger i en organisasjon oppfatninger som medlemmene utvikler sammen og tar for gitt.…”
Section: Også Voksne Mobberunclassified